2007
DOI: 10.1111/j.1365-3121.2007.00773.x
|View full text |Cite
|
Sign up to set email alerts
|

Tectonothermal evolution of a foreland fold and thrust belt: the Cantabrian Zone (Iberian Variscan belt, NW Spain)

Abstract: Analysis of the conodont colour alteration index and the Kübler index of illite allowed us the characterization of four types of very low‐ or low‐grade metamorphism in the Cantabrian Zone (CZ) and determination of their regional and temporal distribution. These types are: (1) an orogenic Variscan metamorphism present only in restricted areas of the western and north‐western parts of the CZ where epizonal conditions are reached; (2) a burial metamorphism that appears in the basal part of some nappes, where anch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 40 publications
(57 reference statements)
4
28
0
3
Order By: Relevance
“…The Permian heating phase in the Sabero Coalfield (Fig. 3) was probably caused by the well-known magmatism and its associated hydrothermal activity under an extensional tectonic regime (Aller et al 2005;García-López et al 1997, 2007. The important heating phase had a significant thermal effect due to a deep source of heat.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The Permian heating phase in the Sabero Coalfield (Fig. 3) was probably caused by the well-known magmatism and its associated hydrothermal activity under an extensional tectonic regime (Aller et al 2005;García-López et al 1997, 2007. The important heating phase had a significant thermal effect due to a deep source of heat.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, new models (Fig. 3) were constructed taking into account previous thermal history studies in the SCZ (García-López et al 1997, 2007Ayllon 2003;Ayllon et al 2003;Frings et al 2004;Aller et al 2005;Frings and Warr 2012;Botor 2012), which indicated that the Late Carboniferous-Permian period was the main heating time. Vitrinite reflectance data were used to calculate the maximum palaeotemperatures (values T max 2 and T max 3 in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, an anchizonal or epizonal E-W band appears in the southern and southeastern parts of the Cantabrian zone. This band is associated with a nearly horizontal or moderately north-dipping cleavage that cuts across the main Variscan folds, and has been related to a late Variscan extensional episode that occurred near the Carboniferous-Permian boundary , 2007Bastida et al 2004). Hydrothermal activity related to normal faults continued during Permian and Mesozoic times.…”
Section: S B L a N C O -F E R R E R A A N D Ot H E R Smentioning
confidence: 95%